Instrucción cívica y formación ciudadana en la educación superior en Colombia durante primera mitad del siglo XX : el caso del Colegio Mayor de Nuestra Señora del Rosario (2017)
The present text analyzes what kind of civic instruction and citizen education training was given in Colegio Mayor de Nuestra Señora del Rosario during the first half of the twentieth century, with the aim of contributing to the current debate on citizenship education in higher education in Colombia. Based on the civil, political, social, economic and cultural dimensions of citizenship, proposed by Juan Manuel Ramírez Sáiz, an exercise of documentary review was carried out, which allowed the tracking of timely information regarding the interests, methodologies, norms and characters that determined the Pedagogical process developed by this institution with the intention of training the new members of society. The results obtained allow us to emphasize the presence of various themes related to each of the dimensions of citizenship proposed by Ramirez in the context of higher education of the twentieth century, refusing those ideas according to which only within the structure and functioning of contemporary states...